Design and simulation of ultra-wideband (uwb) system and proposed a solution to uwb connection in the three- imensional integrated circuits - Nguyen , Chí Nhân; Nguyen , Văn Thái Bình; Duong , Hoài Nghĩa; Dinh , Văn Ánh (Journal of Technical Education Science, 2012)
Today, traditional wire interconnect systems may soon encounter their fundamental material limits. To surpass these fundamental limits, wireless interconnect systems have been proposed, which realize intra-chip interconnection at the speed of light via electromagnetic waves using UWB transceiver. UWB interconnect systems can be used for both clock and data signals [6]. In this paper, we focus on research, design and simulation of UWB transceiver, analyze the factors such as power consumption, the bit error rate (BER) and propose a solution to UWB connection in the three-dimensional integrated circuits